Tinjauan Hukum Terhadap Implementasi Perjanjian Pinjam Meminjam Uang Antara Anggota Dengan Koperasi Serba Usaha (KSU) Bhakti Karya Praya, Kabupaten Lombok Tengah - Ira Sulistya; Wiwiek Wahyuningsih (Fakultas Hukum Universitas Mataram, 2022)
This research aims are to know the implementation of loan agreement between member and multiple business cooperative Bhakti Karya Praya, Central Lombok, also to know dispute settlement mechanism in the loan agreement. The applied method was normative legal search. Research’s result said that implementation of loan agreement between members and cooperative conducted in several phases, are submission of loan applications, filling in data on prospective borrowers, checking loans, evaluating loan applications, making decisions, and monitoring loans. Dispute settlement mechanism in the loan agreement always prioritize the principle of kinship by conducting some efforts, such as collecting the debt at the residence of the debtor, issue a warning letter to the debtor, as wll as retain and sell collateral belonging to the debtor or credit applicant.